Effectiveness of Commuter Rail Service Toward Passenger’s Satisfaction: a Case Study from Kuala Lumpur, Malaysia - Nazrul Hakimi Ibrahim, Ahmad; Nazri Borhan, Muhamad; Asilah Zakaria, Nur; Khairunisa Zainal, Siti (International Journal of Engineering and Technology, 2019)
This paper’s main objective is to evaluate the quality of commuter rail service at Kuala Lumpur by conduction a commuter user survey. The study sample consisted of 400 commuter rail passengers. The results reveal that there is significant conflict between passenger’s expectation and perception of the commuter rail service quality at Kuala Lumpur. Measured value for passenger expectation are found to be consistently higher than their satisfaction, which indicate that is room for Malayan Railways Limited (KTMB) management to improve its service quality. Three out of 12 service items such as the price of ticket, the punctuality time for departure and arrival of train, and ticket counter rated as important and satisfactory, and thus should be maintained. These items are the issues that may have caused concerns for passengers and should urgently addressed by KTMB management to improve passenger’s satisfaction as well as to increase the commuter rail ridership.
Keywords: Importance-performance analysis (IPA); passenger satisfaction; passenger perception; commuter rail; quality of service.